Networking for development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
In the 1970s the UK's Overseas Development Institute (ODI) investigated the possibility of maintaining the international inter-disciplinary contacts established between researchers and practitioners at seminars and conferences. This led to the...